Are we missing out on the demographic dividend? Trends and prospects - Michael R. M. Abrigo; Rachel H. Racelis; J. M. Ian Salas; Alejandro N. Herrin; Danica A. P. Ortiz; Zhandra C. Tam (Philippine Institute for Development Studies (PIDS), 2018)
The Philippines is slowly ageing. In a little over a decade, the country's elderly will comprise at least seven percent of the total population. This rising tide may pose some substantial burden to the country's resources. But the same economic and demographic forces that will eventually lead to population ageing also provide potentials for economic growth. In this paper, we document the country's historical experience of this so-called demographic dividend using new National Transfer Account time-series estimates for the Philippines. We also used these estimates to simulate how the interaction between public policy and population ageing may affect household welfare and fiscal balance in the foreseeable future.
Keywords: 330; Demographic dividend; National Transfer Accounts; Population; Philippines